Pomen digitalne enciklopedije DEDI pri ohranjanju in soustvarjanju slovenske dediščine - Šmid Hribar, Mateja (Etnolog. Nova vrsta (Ljubljana), 2010)
The article presents the website of the Digital Heritage Encyclopaedia called DEDI, which introduces new concepts to the protection and presentation of heritage to the general public. DEDI provides support to scientific-research activities, learning and cultural development, strengthens the national identity, and contributes to Slovenia's recognisability and competitiveness. The encyclopaedia's principal value lies in its integrated presentation of the four types of heritage in one place. Special attention is dedicated to e-learning, the use of the digital encyclopaedia for educational purpose, and the active parcitipation of the widest public - all in the spirit of our motto that we can only preserve what we know.
Keywords: ethnology; etnologija; kulturna dediščina; cultural heritage; naravna dediščina; digitalizacija; digitization; DEDI; e-učenje; e-storitve; spletne strani